Metabolic profiles in C3, C3–C4 intermediate, C4-like, and C4 species in the genus Flaveria. (15th December 2021) - Borghi, Gian Luca; Arrivault, Stéphanie; Günther, Manuela; Barbosa Medeiros, David; Dell'Aversana, Emilia; Fusco, Giovanna Marta; Carillo, Petronia; Ludwig, Martha; Fernie, Alisdair R; Lunn, John E; Stitt, Mark
Abstract: C4 photosynthesis concentrates CO2 around Rubisco in the bundle sheath, favouring carboxylation over oxygenation and decreasing photorespiration. This complex trait evolved independently in >60 angiosperm lineages. Its evolution can be investigated in genera such as Flaveria (Asteraceae) that contain species representing intermediate stages between C3 and C4 photosynthesis. Previous studies have indicated that the first major change in metabolism probably involved relocation of glycine decarboxylase and photorespiratory CO2 release to the bundle sheath and establishment of intercellular shuttles to maintain nitrogen stoichiometry. This was followed by selection for a CO2 -concentrating cycle between phospho enol pyruvate carboxylase in the mesophyll and decarboxylases in the bundle sheath, and relocation of Rubisco to the latter. We have profiled 52 metabolites in nine Flaveria species and analysed 13 CO2 labelling patterns for four species. Our results point to operation of multiple shuttles, including movement of aspartate in C3 –C4 intermediates and a switch towards a malate/pyruvate shuttle in C4 -like species. The malate/pyruvate shuttle increases from C4 -like to complete C4 species, accompanied by a rise in ancillary organic acid pools. Our findings support current models and uncover further modifications of metabolism along the evolutionary path to C4 photosynthesis in the genus Flaveria . Abstract : Metabolite profiling and 13 CO2 labelling studies of Flaveria species on the spectrum between C3 and C4 photosynthesis reveal progressive re-wiring of photorespiration, nitrogen metabolism, carbon concentration shuttles, and the Calvin–Benson cycle.